Triadism Perspective on Payment of Debt Taxes in Complete Systematic Hold Registration Program: What and How? - Adytia, Nur Amalina Putri; Anshari SN, Tunggul; Jauharoh, Arini (Universitas Muhammadiyah Sidoarjo, 2022)
The Complete Systematic Land Registration Program (PTSL) actually has an orientation to provide guarantees of legal certainty. However, the formulation of rules in Ministerial Regulation No. 6/2018 regarding PTSL provides space for not fulfilling three values that must be met by law. This study aims to analyze PTSL Regulations in the perspective of Gustav Radbruch's triadism. This research is a juridical-normative research by prioritizing conceptual and statutory approaches. The results of the study confirmed that from the aspects of fairness, benefit, and legal certainty, the regulation of the payment of taxes payable for the transfer of rights to certified land from the PTSL program as stated in the PTSL Ministerial Regulation has the potential to prevent the three basic legal values from being realized. The non-realization of the three basic legal values above in the formulation of arrangements for payment of taxes payable for the transfer of land rights certified from the PTSL program has the potential to cause injustice in society while minimizing the beneficial aspects of the PTSL program as well as creating legal uncertainty in society regarding the implementation of the PTSL program which has the potential to harm human rights. community as PTSL participants. Revisions to the PTSL Ministerial Regulation, specifically Article 33 paragraph (1) of the PTSL Ministerial Regulation in conjunction with Article 40 paragraph (1) of the PTSL Ministerial Regulation actually aim to fulfill the three basic legal values put forward by Gustav Radbruch, for ensuring justice, expediency, and legal certainty.